Post-treatment Clinical Outcomes of Cutaneous Leishmaniosis in the Bam Area, South Eastern Iran: Analysis of over 9,000 Cases - Erfan Ayubi; Ahad Ashrafi-Asgarabad; Saeid Safiri; Ahmad Kousha; Mohammad Baniasadi; Christoph Augner (International Journal of Infectious Diseases, 2015)
Background: Knowledge about risk or protective factors for post-treatment outcomes in Cutaneous Lishmaniosis are rare, especially in endemic areas such as Iran. The present study aimed to evaluate the association between the outcome of infection, clinical manifestation, and treatment with adverse post-treatment outcomes in Cutaneous Lishmaniosis patients. Methods: This was a cross sectional study based on recently collected data of 9077 Cutaneous Lishmaniosis patients (4585 female and 4492 male) from March 2003 to March 2011 in the Bam area, Iran. Multivariable multinomial logistic regression was applied to assess the effect of outcome of infection, clinical manifestation and treatment on relapse, treatment after interruption, treatment failure and clinical resistance. Results: Head lesions were strongest risk factor for relapse (Odds Ratio, OR=4.21; CI 95%: 3.56-4.98), treatment after interruption (2.00; 1.70-2.35), treatment failure (6.61; 5.17-8.45) and clinical resistance (2.62; 2.00-3.44). Family occurrence (yes vs. no), intra lesion therapy method, treatment duration (>3 v. ≤ 3 week) and source of detection by Surveillance (active vs. passive), were the most protective factors for relapse (OR=0.58; CI 95%: 0.46-0.74), treatment after interruption (0.36; 0.31-0.42) treatment failure (0.24; 0.20-0.29) and clinical resistance (0.24; 0.09-0.67). Conclusion: Head lesions and treatment variables (e.g. therapy method and duration) could predict the occurrence of adverse post-term outcomes of Cutaneous Lishmaniosis. Further longitudinal studies have to clarify cause and effect relationships.